Effect of Poguntano leaves extract (Picria fel-terrae Merr.) to procalcitonin level in acute bacterial rhinosinusitis model of Wistar mice - Andrina Yunita Murni Rambe; Delfitri Munir; Rosita Juwita Sembiring; Syafruddin Ilyas (Medicinski glasnik, 2019)
Aim: Acute rhinosinusitis (AR) is of viral aetiology and only 0.5-2% develop into acute bacterial rhinosinusitis. Herbal therapy is a promising alternative in acute bacterial rhinosinusitis treatment. The aim of this study was to evaluate the effect of ethanol extract of Poguntano leaves (EEPL) to procalcitonin level and the amount of bacteria in acute bacterial rhinosinusitis mice model. Methods: Experimental research with posttest only control group design in 32 Wistar mice that were divided into 4 groups, 3 of which were being inoculated with Staphylococcus aureus by inserting a sponge to right nasal cavity of the mice (group K2, K3, and K4); another one was the negative control group (K1). Group K2 was not given any kind of therapy (positive control), group K3 was given 10 mg/kd EEPL for 5 days orally during an induction, and group K4 was given 10 mg/kd EEPL for 5 days orally on the 10th day after induction. Mice in the groups K2 and K3 were sacrificed on the 10th day after induction, while mice in group K4 were sacrificed on the 15th day after induction. Result: A statistically significant decrease in procalcitonin level (p<0.001) and amount of bacterial colony (p<0.001) was found in four groups. Conclusion: Poguntano leaves extract can lower procalcitonin and amount of bacteria colony, showing an anti-inflammatory and antibacterial effect.
Keywords: immunology; inflammation; microbiology; therapeutics; rhinitis